Experience of Parents of Children with Genetically Determined Leukoencephalopathies Regarding the Adapted Health Care Services During the COVID-19 Pandemic. (March 2022) - Amir Yazdani, Pouneh; St-Jean, Marie-Lou; Matovic, Sara; Spahr, Aaron; Tran, Luan T.; Boucher, Renée-Myriam; Poulin, Chantal; Osterman, Bradley; Srour, Myriam; Rosenblatt, Bernard; Chenier, Sébastien; Soucy, Jean-Francois; et al.
Parents of children with genetically determined leukoencephalopathies play a major role in their children's health care. Because of the COVID-19 pandemic, many health care services were suspended, delayed or delivered remotely with telemedicine. We sought to explore the experience of parents of children with genetically determined leukoencephalopathies during the pandemic given the adapted health care services. We conducted semistructured interviews with 13 parents of 13 affected children. Three main themes were identified using thematic analysis: perceived impact of COVID-19 on health care services, benefits and challenges of telemedicine, and expectations of health care after the pandemic. Parents perceived a loss/delay in health care services while having a positive response to telemedicine. Parents wished telemedicine would remain in their care after the pandemic. This is the first study assessing the impact of COVID-19 on health care services in this population. Our results suggest that parents experience a higher level of stress owing to the shortage of services and the children's vulnerability.